Bending testing of Pulai (Alstonia Angustiloba) - Mohd Salleh, Fairuz; Othman, Mohd Hanif; Abdul Halim, Mohd Hasri; Mohamed, Suhaila (2008)
It is important to study wood and its characterization in order to reach a good utilization of this material. In Malaysia, wood is one of the source of income and it is still use widely as the construction especially in the housing sector such as roof system. It is because wood easy to work, durability and attractive. Beside that, wood can absorb the load which occurred with the shock way and the wood not have rust. The Pulai species are selected to know either this species suitable or not to make various uses. This testing on the specimen is bending strength, Modulus of Elastic (MOE) and Modulus of Repture (MOR).